2014
DOI: 10.4067/s0370-41062014000600008
|View full text |Cite
|
Sign up to set email alerts
|

Trombosis de vena cava inferior y endocarditis en un paciente prematuro: Caso clínico

Abstract: inferior vena cava thrombosis and endocarditis in a premature patient -Case reportThrombosis of the inferior vena cava represents a significant percentage of all venous thrombosis that take place during the neonatal period, generally associated with risk factors such as the use of central venous catheter. The incidence of bacterial endocarditis in preterm infants is low. objectives: To characterize the case of a preterm neonate with both conditions and to detail the disease changing spectrum in the neonatal po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…IVCST is an uncommon condition that is often associated with surgical procedures, implantation of vascular foreign bodies, intravenous drug use, and tumor invasion [1][2][3][4][5][6][7] . In one reported case, the condition was secondary to Crohn's disease 8 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…IVCST is an uncommon condition that is often associated with surgical procedures, implantation of vascular foreign bodies, intravenous drug use, and tumor invasion [1][2][3][4][5][6][7] . In one reported case, the condition was secondary to Crohn's disease 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In the course of the disease, different pathogens may be cultured at different times in the same patient. Reported cases have identi ed bacteria such as Enterococcus, Staphylococcus, Streptococcus, Klebsiella, Bacteroides, Actinomyces, and Enterobacteriaceae coli, as well as Candida as the most common gram-positive bacteria and fungi, respectively [1][2][3][4][5][6][7][8] . Buitrago AP et al reported a case of an infant with IVC thrombosis and infective endocarditis (IE) resulting from umbilical vein catheterization 5 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations